Comparación de las Propiedades Mecánicas Carga- Deflexión y Tensión - Esfuerzo de los Alambres de Ortodoncia GUMMETAL® y CuNiTi (2021)
This study was carried out by using a sample of sixty transversal -section orthodontic wires, 0.017x 0.025 inches gauge; thirty were GUMMETAL® alloy and thirty were thermoactivated CuNiTi in order to evaluate and compare variables by load-deflection and Stress -Strain. Samples were evaluated and compared by tensile tests on the Shimadzu® AG-IS universal mechanical testing machine. It was possible to establish that GUMMETAL® has a much higher elastic limit; with regard to the force, it was possible to determine that GUMMETAL® shows a lower and constant force; with the variable 'stiffness' CuNiTi showed a low but less stable stiffness, while GUMMETAL® on the contrary showed a higher stiffness but at the same time more constant; CuNiTi showed a much higher but more unstable range, and GUMMETAL® showed a much smaller but more stable range.